HEALTH TOURISM IN BELITUNG INDONESIA: A SWOT ANALYSIS - Joko Gunawan; Nur Asni Wahab; Elmiati Elmiati (Belitung Nursing Journal, 2016)
This article aims to provide the development strategy to see the possibility of providing health tourism in Belitung Indonesia. The Strength, Weakness, Opportunity, and Threat are provided as basic information for the action plans that consist of human resource, products, and governance.